Effectiveness of four dynamic treatment strategies in patients with anticitrullinated protein antibody-negative rheumatoid arthritis: a randomised trial. Issue 1 (25th March 2016) - Akdemir, G; Markusse, IM; Dirven, L; Riyazi, N; Steup-Beekman, GM; Kerstens, PJSM; Lems, WF; Huizinga, TWJ; Allaart, CF
Abstract : Objective: To determine the most effective treatment strategy among anticitrullinated protein antibodies (ACPA)-negative patients with early rheumatoid arthritis. Methods: In the BeSt study, 184 ACPA-negative patients were randomised to: (1) sequential monotherapy, (2) step-up therapy, (3) initial combination including prednisone, (4) initial combination including infliximab. Treatment was targeted at the disease activity score (DAS) ≤2.4. Early response and 10-year outcomes were compared between the four strategy-arms in ACPA-negative patients. Results: ACPA-negative patients achieved more short-term functional improvement from initial combination therapy than when on monotherapy (at month 3, mean Health Assessment Questionnaire (HAQ) 0.71 vs 0.98, p=0.006; at month 6, 0.59 vs 0.87, p=0.004). Functional ability over time was comparable between the strategy-arms (p=0.551) with a mean HAQ of 0.6 at year 10 (p=0.580 for comparison across the strategy-arms). 10-year radiographic progression was negligible (median 0.5) and comparable between the 4 strategy-arms (p=0.082). At year 10, remission was achieved by 11/40 (28%), 9/45 (20%), 17/56 (30%) and 17/43 patients (40%) in strategy-arms 1–4, respectively (p=0.434). Over time, similar remission percentages were achieved in all strategy-arms (p=0.815). 18%, 16%, 20% and 21% in strategy-arms 1 to 4 (p=0.742) were in drug-free remission at year 10, with a median duration of 60 months across the arms. Conclusions: Initial combination therapy with methotrexate, sulfasalazine and prednisone, or methotrexate and infliximab, is the most effective treatment strategy for ACPA-negative patients, resulting in earlier functional improvement than when on initial methotrexate monotherapy. After 10 years of targeted treatment, in all strategy-arms favourable clinical outcomes were achieved and radiographic progression was limited. Trial registration number: NTR262, NTR265.